2020
DOI: 10.1002/fsn3.1493
|View full text |Cite
|
Sign up to set email alerts
|

Microwave cooking increases sulforaphane level in broccoli

Abstract: Sulforaphane (SFR), an anticarcinogenic compound, forms from the hydrolysis of glucoraphanin (GLR) in broccoli. Cooking methods have been shown to affect broccoli GLR and SFR levels, but little is known about the effect of lightly cooking processes on them. In this study, the effects of microwave and low-temperature cooking on GLR and SFR contents in broccoli were investigated. Both microwaving and mild heating increased the GLR and SFR levels in broccoli compared to the raw samples (without any treatment). In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…To note, there were no detectable ITCs in the cooking water from boiling, stewing, and steaming in our study (results not shown). Interestingly, microwaving and steaming were reported to increase the level of glucosinolates (Gliszczyńska-Świgło et al, 2006;Lu, Pang, & Yang, 2020), which was assumed that mild-heating causes disintegration of plant tissues, thus leads to more release of glucosinolates (Nugrahedi, Verkerk, Widianarko, & Dekker, 2015). However, the potential contribution (Jiao et al, 1994;Navarro, Li, & Lampe, 2011;Singh & Singh, 2012;Wang et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…To note, there were no detectable ITCs in the cooking water from boiling, stewing, and steaming in our study (results not shown). Interestingly, microwaving and steaming were reported to increase the level of glucosinolates (Gliszczyńska-Świgło et al, 2006;Lu, Pang, & Yang, 2020), which was assumed that mild-heating causes disintegration of plant tissues, thus leads to more release of glucosinolates (Nugrahedi, Verkerk, Widianarko, & Dekker, 2015). However, the potential contribution (Jiao et al, 1994;Navarro, Li, & Lampe, 2011;Singh & Singh, 2012;Wang et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Proper heating treatment can reduce ESP activity and the production of sulforaphane nitrile as well as allow for more production of sulforaphane [19] . It has been reported that ESP was inactivated after heating for 5–10 min at 60–70 ℃, while myrosinase was inactivated after heating for 5–15 min at 100℃ [20] .…”
Section: Resultsmentioning
confidence: 99%
“…Epithionitriles are formed from GSLs containing an unsaturated terminal side chain [ 17 ]. Different cooking conditions and food matrices (such as heating time and temperature, microwaving time and power level, volume of water added, and cutting size) impact the chemical composition of the food ingested, the conversion of GSLs to ITCs, and thus the extent of bioactivity [ 15 , 19 , 20 ]. For example, sulforaphane (SF, the ITC metabolite of GRP) production from broccoli sprouts is significantly increased by preheating the sprouts to 60 °C for 10 min, destroying the very heat-sensitive ESP (the plant protein that favors the formation of nitriles over ITCs during hydrolysis).…”
Section: Metabolism Of Glucosinolates and Resulting Itc Bioavailabili...mentioning
confidence: 99%